Innovating Against The Odds: Unveiling The Production Process And Critical Factors Behind Rote Ndao’s Stunting Prevention Innovations. - Lengga, Herianus; Pradana, I Putu Yoga Bumi; Djaha, Ajis Salim Adang (JURNAL TRIAS POLITIKA, 2025)
This study investigates the production process of public sector innovation in addressing stunting prevalence in Rote Ndao Regency, a topic that remains underexplored by public sector innovation scholars. Employing a qualitative approach with a multiple case study method, this research involved in-depth interviews with 20 informants directly engaged in two innovation initiatives: the Ka’a Fadi Innovation implemented by the PMD Office and the Mama Bo’i Innovation developed by the Health Office. The study identifies four key stages in the innovation production process: idea production, idea transformation into a prototype, championing for support, and integrating the prototype into formal policy. The findings reveal distinct differences in the production process and critical factors influencing the realization of these innovations. The Ka’a Fadi Innovation follows three stages of the production process. Four critical factors influence it, while the Mama Bo’i Innovation progresses through all four stages, supported by the same four critical factors. These determinants include transformational leadership, resource management, innovation characteristics, and external environment. The novelty of this research lies in its identification of unique production processes and key determinants that facilitate public sector innovation in resource-constrained local government settings. This study offers valuable insights into strategies for fostering public innovation in regions with limited resources, contributing to the broader discourse on public sector innovation.